Decoding the chain of effects of family firm image on consumer behaviour. Issue 5 (17th February 2021) - Köhr, Christopher Karl; Corsi, Armando Maria; Capitello, Roberta; Malorgio, Giulio
Abstract: While there has been plenty of research around family firm governance and management, less is known about the way in which family firm image is perceived by consumers. This research aims at filling the gap by investigating the chained links between family firm status and image, and the key brand elements identified by extant literature. The hypotheses are tested through an application to the wine industry with a sample of over 1, 500 wine drinkers residing in Australia, Italy, and the United States. The results reveal several linkages between the distinctive family nature of a business and the loyalty of consumers. All brand knowledge constructs are positively affected by family firm image, and influence brand trust and satisfaction. Individual path coefficients highlight differences between countries. Evidence regarding the cultural interdependencies provides guidance for policy makers. Practitioners can consider this research when defining the relationship with consumers of family firms.